Senegal : Second Review Under the Policy Coordination Instrument and Request for Modification of Quantitative Targets-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Although the pandemic has remained fairly contained in Senegal, its economic impact has been severe. Strong fiscal and monetary policy support has helped bolster the health system and cushion the economic shock, with additional fiscal spending exceeding 3 percent of GDP. The IMF disbursed USD 442 million (100 percent of quota) under the RFI/RCF in April to support the crisis response. An ambitious 2021-23 economic recovery plan aims to build a more resilient economy and support inclusive and private sector-led growth. WAEMU Finance Ministers agreed to return to the 3 percent of GDP fiscal deficit anchor more gradually (by 2023) owing to the pandemic's impact and the security challenges in the Sahel.